2001
DOI: 10.1542/peds.107.3.e34
|View full text |Cite
|
Sign up to set email alerts
|

Racial Divergence in Adiposity During Adolescence: The NHLBI Growth and Health Study

Abstract: ABSTRACT. Background. Black women are particularly vulnerable to obesity, with a prevalence rate of >50%. The higher mortality and morbidity from cardiovascular disease, stroke, and diabetes have been attributed, in part, to their obesity. In recent years, a particular public health concern is the increasing secular trend in obesity with an even greater racial disparity, especially in girls and women. Between the early 1960s and late 1980s, the prevalence of obesity tripled in young black girls 6 to 11 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
128
1
6

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 28 publications
13
128
1
6
Order By: Relevance
“…While perhaps counterintuitive, weak or no relations of EI and general adiposity have been reported, 20 suggesting that a positive EB is mainly the result of a low EE. 36 Inverse relations between EI and adiposity have been shown by others, 37 lending support to the results of this study. Underreporting of EI in youth is a phenomenon which could in part explain conflicting results between studies of diet and adiposity, and could obscure existing relationships.…”
Section: Dietary Factorssupporting
confidence: 91%
“…While perhaps counterintuitive, weak or no relations of EI and general adiposity have been reported, 20 suggesting that a positive EB is mainly the result of a low EE. 36 Inverse relations between EI and adiposity have been shown by others, 37 lending support to the results of this study. Underreporting of EI in youth is a phenomenon which could in part explain conflicting results between studies of diet and adiposity, and could obscure existing relationships.…”
Section: Dietary Factorssupporting
confidence: 91%
“…The absence of a significant relationship between physical activity and OW found in the preadolescent and adolescent groups is only partially shared in the literature. Crosssectional and longitudinal studies are roughly divided between finding no effect (McMurray et al, 1995;Goran et al, 1997;Maffeis et al, 1998;Kimm et al, 2001), or a protective effect of activity (Moore et al, 1995;Hernandez et al, 1999;Berkey et al, 2000;O'Loughlin et al, 2000;Tremblay and Willms, 2003;Janssen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Maturational timing has been consistently shown to be associated with obesity -those reporting early onset of puberty becoming more obese (73)(74)(75)(76). The US National Heart, Lung and Blood Institute (NHLBI) growth and health study showed that the large difference in obesity between the black and white American girls emerged during puberty and that the early onset of menarche in the black girls in part explained their higher fat mass (77). Whether these associations with pubertal onset represent an effect of maturational timing on fat and lean mass or are an effect of fat and lean mass on maturational timing requires investigation in longitudinal studies with accurate measures of body composition before and after puberty.…”
Section: Puberty and Childhood Obesitymentioning
confidence: 99%